Public baths and bathing habits in late antiquity : a study of the evidence from Italy, North Africa and Palestine A.D. 285-700 - Maréchal, Sadi (Late antique archaeology. Supplementary series, 2020)
"In this book Sadi Maréchal examines the survival, transformation and eventual decline of Roman public baths and bathing habits in Italy, North Africa and Palestine during Late Antiquity. Through the analysis of archaeological remains, ancient literature, inscriptions and papyri, the continued importance of bathhouses as social hubs within the urban fabric is demonstrated, thus radically altering common misconceptions of their decline through the rise of Christianity and elite seclusion. Persistent ideas about health and hygiene, as well as perpetuating ideas of civic self-esteem, drove people to build, restore and praise these focal points of daily life when other classical buildings were left to crumble."--